Degradation in chlorinated water of the UV filter 4-tert-butyl-4'-methoxydibenzoylmethane present in commercial sunscreens - Crista, Diana M A (Environmental technology, 2015)
4-tert-Butyl-4'-methoxydibenzoylmethane (BMDM) is a widely used ultraviolet A filter. In this work, we have studied the effect of chlorine and dissolved organic matter (DOM) concentrations on the stability of UV filter (BMDM) present in two commercial sunscreen cream formulations in water. An experimental design was used to assess the effect of the two experimental factors on the degradation of BMDM. Higher concentrations of chlorine lead to higher degradation percentages of BMDM and higher concentrations of DOM inhibit its degradation. Moreover, a mono and a dichloro derivate of BMDM were identified as by-products